2019
DOI: 10.1017/prp.2018.30
|View full text |Cite
|
Sign up to set email alerts
|

Mobilising Men: Ally Identities and Collective Action in Japan and the Philippines

Abstract: M en have an important role as allies in reducing discrimination against women. Following the Social Identity Model of Collective Action (SIMCA), we examined whether men's identification with women would predict their allied collective action, alongside moral convictions, efficacy, and anger. We also examined whether identification with their own ingroup would decrease their willingness to improve women's situation. We tested the SIMCA, extended to consider ingroup identification among men, in Japan (N = 103) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Thus, akin to the effects of perspective taking, to the extent that a person identifies with the disadvantaged group (even though they do not identify as a member of that group in the terms of the social identity approach), this may stimulate action in solidarity with that group (e.g., Stewart et al, 2015; van Zomeren et al, 2011). Thus, collective action is fostered for members of advantaged groups when they take that (disadvantaged group) perspective (Ochoa et al, 2019), although the relationship continues to be an intergroup one (Figure 2a).…”
Section: Primary Citation Name Of Model Key Paths and Their Interrela...mentioning
confidence: 99%
“…Thus, akin to the effects of perspective taking, to the extent that a person identifies with the disadvantaged group (even though they do not identify as a member of that group in the terms of the social identity approach), this may stimulate action in solidarity with that group (e.g., Stewart et al, 2015; van Zomeren et al, 2011). Thus, collective action is fostered for members of advantaged groups when they take that (disadvantaged group) perspective (Ochoa et al, 2019), although the relationship continues to be an intergroup one (Figure 2a).…”
Section: Primary Citation Name Of Model Key Paths and Their Interrela...mentioning
confidence: 99%
“…This model explains how, by developing shared higher‐order identities (e.g., men and women as “agents of change”), gender inequality can be seen as a common social problem standing in the way of social justice for all (Subašić et al, 2018). Men, as members of the advantaged gender group, might be more willing to become allies in the struggle for social justice when they share the disadvantaged group's view that existing gender inequalities are illegitimate (Becker, Wright, Lubensky, & Zhou, 2013), and that ending gender‐based discrimination is consistent with their moral convictions (Ochoa, Manalastas, Deguchi, & Louis, 2019). Through this lens, people of all genders are both sources and beneficiaries of gender equality.…”
Section: Men's Roles In Gender Equalitymentioning
confidence: 99%
“…A study with a Chinese sample reported that for those who belonged to a lower-status group, there was no significant relationship between anger at group injustice and collective action intentions [17]. The identical relationship was also established among Filipino and Japanese males in relation to a sexist scenario [18]. Together with the tendency to avoid collective action of Indonesian low-status group mentioned above [14], these results supported the notion that a high level of power distance in Asian cultures offered no or little hope and scope for social change as inequalities (e.g., sexism and power structure) were legitimized.…”
Section: The Social Identity Model Of Collective Action In the Asian mentioning
confidence: 97%